2009
DOI: 10.1158/1078-0432.ccr-08-3272
|View full text |Cite
|
Sign up to set email alerts
|

PF-00477736 Mediates Checkpoint Kinase 1 Signaling Pathway and Potentiates Docetaxel-Induced Efficacy in Xenografts

Abstract: Purpose: Checkpoint kinase 1 (Chk1) plays a critical role in the activation of mitotic spindle checkpoint and DNA damage checkpoint. We examined the preclinical use of the Chk1 inhibitor PF-00477736 as a docetaxel-sensitizing agent. Specifically, we investigated the correlation between PF-00477736^mediated modulation of biomarkers and the sensitization of docetaxel efficacy. Experimental Design: In vitro and in vivo studies using COLO205 and other cell lines were done to assess PF-00477736^induced enhancement … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 42 publications
1
39
0
Order By: Relevance
“…Therefore, we examined the in vivo tolerability of the dual and triple combinations. Because we and others (21) have found that concurrent treatment was effective, we administered CHK1i concurrently with gemcitabine instead of a 24-hour delay (7). Dosing schedules of 50 mg/kg gemcitabine and 15 mg/kg (7.5 mg/kg twice daily, b.i.d.)…”
Section: Tolerability and Efficacy Of Gemcitabine Chk1i And Egfr-dimentioning
confidence: 99%
“…Therefore, we examined the in vivo tolerability of the dual and triple combinations. Because we and others (21) have found that concurrent treatment was effective, we administered CHK1i concurrently with gemcitabine instead of a 24-hour delay (7). Dosing schedules of 50 mg/kg gemcitabine and 15 mg/kg (7.5 mg/kg twice daily, b.i.d.)…”
Section: Tolerability and Efficacy Of Gemcitabine Chk1i And Egfr-dimentioning
confidence: 99%
“…FLT-PET and CT imaging was done using a microPET Focus F220 scanner (Siemens Medical Solutions) and a GE eXplore microCT scanner (GE Healthcare), respectively, as described previously (21). Tumor-bearing mice were anesthetized and administered 250 mCi (1-2 mg/kg) of […”
Section: Immunohistochemical Stainingmentioning
confidence: 99%
“…Other selective Chk1 inhibitors were also shown to abrogate the S-phase delay induced by topoisomerase inhibitors (Chen et al, 2006;Tse et al, 2007) and to potentiate the cytotoxicity of g-radiation in p53-deficient cells (Chen et al, 2006). These effects were associated with increased mitotic entry, induction of DSB and apoptosis, as well as marked inhibition of proliferation (Chen et al, 2006;Tse et al, 2007;Blasina et al, 2008;Zhang et al, 2009). The synergy between replication stress inducers and Chk1 inhibitors was translated into a dose-dependent increase in tumor growth delay in vivo (Tse et al, 2007;Blasina et al, 2008;Zhang et al, 2009).…”
Section: Combinations Of Dna-repair Inhibitorsmentioning
confidence: 99%
“…These effects were associated with increased mitotic entry, induction of DSB and apoptosis, as well as marked inhibition of proliferation (Chen et al, 2006;Tse et al, 2007;Blasina et al, 2008;Zhang et al, 2009). The synergy between replication stress inducers and Chk1 inhibitors was translated into a dose-dependent increase in tumor growth delay in vivo (Tse et al, 2007;Blasina et al, 2008;Zhang et al, 2009).…”
Section: Combinations Of Dna-repair Inhibitorsmentioning
confidence: 99%